2018
DOI: 10.1186/s12885-018-4677-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of insulin-like growth factor-1 as a prognostic parameter in patients with hepatocellular carcinoma in a European cohort

Abstract: BackgroundIn hepatocellular carcinoma (HCC), the third leading cause of cancer-related mortality worldwide, the Child-Turcotte-Pugh score (CTP) is one of the most established tools to assess hepatic reserve and determine survival. Serum levels of insulin-like growth factor-1 (IGF-1) are decreased in patients with chronic liver disease or HCC. A modified score combining circulating IGF-1 with the CTP score (IGF-CTP) was recently proposed.MethodsIGF-CTP scoring was evaluated in 216 patients diagnosed with HCC be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The liver, which is crucial in whole-body metabolic homeostasis, has been shown to participate in causing skeletal muscle wasting when compromised (Anand, 2017;Bhanji et al, 2017;De Bandt et al, 2018). Two hepatokines known to play a role in skeletal muscle homeostasis and pathogenesis of multiple diseases, including cancer cachexia, are the anabolic factor IGF1 and the catabolic factor IL6 (Song et al, 2013;Attard-Montalto et al, 1998;Bonetto et al, 2013;Costelli et al, 2006;Cho et al, 2013;Huber et al, 2018). The data presented in the current study support the notion that formation of LM, as occurring in CRC, may further perturb the hepatic production of IGF1 and IL6, thus exacerbating the potential for muscle wasting (Norris et al, 2014;Bonetto et al, 2012Bonetto et al, , 2011Ueda et al, 1994;Baltgalvis et al, 2009;White et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The liver, which is crucial in whole-body metabolic homeostasis, has been shown to participate in causing skeletal muscle wasting when compromised (Anand, 2017;Bhanji et al, 2017;De Bandt et al, 2018). Two hepatokines known to play a role in skeletal muscle homeostasis and pathogenesis of multiple diseases, including cancer cachexia, are the anabolic factor IGF1 and the catabolic factor IL6 (Song et al, 2013;Attard-Montalto et al, 1998;Bonetto et al, 2013;Costelli et al, 2006;Cho et al, 2013;Huber et al, 2018). The data presented in the current study support the notion that formation of LM, as occurring in CRC, may further perturb the hepatic production of IGF1 and IL6, thus exacerbating the potential for muscle wasting (Norris et al, 2014;Bonetto et al, 2012Bonetto et al, , 2011Ueda et al, 1994;Baltgalvis et al, 2009;White et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in patients with liver cirrhosis, the low-affinity of the GH receptor in the liver could induce the resistance of GH stimulation and decrease IGF-1 secretion [ 76 ]. It has been reported that the level of IGF-1 in the plasma of healthy 61 to 75 year old individuals ranges from 61 to 210 μg/mL [ 77 ], while it ranges from 27.7 to 68.6 μg/mL in patients with HCC [ 78 ]. Thereafter, the low levels of IGF-1 would lead to an increase in GH production by positive feedback [ 74 ].…”
Section: Igf/igf-1 Signaling In Hccmentioning
confidence: 99%
“…Although not statistically significant in all categories, possibly due to the small number of patients in our study which was not powered to assess specific parameter correlation, these results were consistent with two previous studies. 30 , 31 Therefore, in contrast to Kaseb et al (2014) study, the current study shows that among tumor patient’s characteristics, tumor nodularity (uni- or multi-nodularity), largest tumor size, tumor metastatic status, and the BCLC stage had no significant correlation with serum IGF-1 levels; however, first-line treatment modality, which was significantly different in terms of survival rates, had a significant correlation with serum IGF-1 levels in the present study which is consistent with IGF-1 predictive value in HCC. Furthermore, low serum IGF-1 levels have been reported to be associated with extensive liver involvement and vascular invasion in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-CTP score allocated the majority of patients into high-risk group C. This reassignment did not improve the prediction of OS, and the C-index analysis showed no relevant improvement in prediction. 31 However, the study population was very heterogeneous since it included 28.3% early-intermediate stage patients, defined as BCLC stages 0-B, in addition to 20% of terminal stage patients, defined as BCLC stage D, which may have independently affected patients survival as well, Table 6 . Similarly, in our current cohort, 38.1% were classified as BCLC stages 0-B, while the majority of the US validation cohort (Kaseb et al, 2014) were classified as advanced HCC, BCLC stage C; 76.8%.…”
Section: Discussionmentioning
confidence: 99%